2021
DOI: 10.1152/japplphysiol.00152.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac baroreflex dysfunction in patients with pulmonary arterial hypertension at rest and during orthostatic stress: role of the peripheral chemoreflex

Abstract: The baroreflex integrity in early-stage pulmonary arterial hypertension (PAH) remains uninvestigated. A potential baroreflex impairment could be functionally relevant and possibly mediated by enhanced peripheral chemoreflex activity. Thus, we investigated 1) the cardiac baroreflex in non-hypoxemic PAH; 2) the association between baroreflex indexes and peak aerobic capacity (i.e., V̇O2peak); and 3) the peripheral chemoreflex contribution to the cardiac baroreflex. Nineteen patients and 13 age- and sex-matched h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Moreover, peripheral chemoreceptors will be stimulated if the patient presents with exercise-induced hypoxemia. In this sense, our group and others have shown synergistic interactions between mechanisms involved in the neural control of ventilation during exercise in healthy humans (24,48), which seem to be potentiated by the presence of cardiorespiratory diseases (33,49,50). Therefore, during active exercise, when the mechanoreflex is activated to a greater extent and plausibly interacts with other neural mechanisms, the mechanoreflex drive to breathe could be of greater magnitude, thereby potentially contributing to the origin of exertional dyspnea and, ultimately, exercise intolerance in patients with COPD.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, peripheral chemoreceptors will be stimulated if the patient presents with exercise-induced hypoxemia. In this sense, our group and others have shown synergistic interactions between mechanisms involved in the neural control of ventilation during exercise in healthy humans (24,48), which seem to be potentiated by the presence of cardiorespiratory diseases (33,49,50). Therefore, during active exercise, when the mechanoreflex is activated to a greater extent and plausibly interacts with other neural mechanisms, the mechanoreflex drive to breathe could be of greater magnitude, thereby potentially contributing to the origin of exertional dyspnea and, ultimately, exercise intolerance in patients with COPD.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, an impaired baroreflex (16) and chemoreflex (25) sensitivities are associated with disease severity in PAH. Otherwise, it was suggested that the peripheral chemoreflex was not a direct mediator of cardiac baroreflex dysfunction in PAH (26). Thus, the sympathetic overactivity in LHD and PAH could be explained, in part, because of a compensatory response from an augmented neurohumoral activation to compensate harmed cardiac output mechanics (27).…”
Section: Autonomic Nervous System and Cardiopulmonary Mechanics In Sy...mentioning
confidence: 99%
“…Autonomic cardiovascular function has been studied in patients with PAH and impaired baroreflex function and increased sympathetic activity has been described [9][10][11][12]. However, the role of autonomic cardiovascular disturbance in progression of PAH or right ventricular dysfunction is not fully understood.…”
Section: Introductionmentioning
confidence: 99%